Concurrent multiple health risk behaviors among adolescents in Luangnamtha province, Lao PDR - Thomsen Sarah; Sychareun Vanphanom; Faxelid Elisabeth (BMC, 2011)
Abstract Background Multiple health risk behaviors (HRBs) among adolescents pose a threat to their health, including HIV/AIDS. Health risk behaviors such as alcohol use, smoking, substance use, and sexual risk behaviors among youth have been shown to co-occur with each others. The objectives of this study was to estimate the prevalence of single and concurrent health risk behaviors and to explore how health risk behavior is associated with socio-demographic factors and peers' behaviors. Methods A cross sectional design was used to examine health risk behaviors of adolescents between the age 14 and 19 years living in the Luangnamtha province, Lao PDR. The study was conducted between June and August, 2008. An ordinal logistic regression model that simultaneously explored demographic factors and the influence of the behavior of peers on three categories of multiple HRBs (no risk, one risk, and two or more health risk behaviors) was performed. Results A total of 1360 respondents, 669 (49.1%) boys with mean age 16.7 ± 1.6 and 699 (50.9%) girls aged 16.1 ± 1.5 were recruited into the study. The majority reported two or fewer risk behaviors. However, multiple risk behaviors increased with age for both sexes. About 46.8% (n = 637) reported no risk, 39.3 percent (n = 535) reported one risk, 8.1 percent (n = 110) reported two risks, and 5.8 percent reported more than two health risk behaviors. The protective factors among boys were school attendance (OR = .53, CI = .33-.86), being Hmong and Yao ethnicity (OR = .48, CI-.26-.90), while being above the age of 15 (OR = 2.20, 95% CI = 1.33-3.60), Akha ethnicity (OR = 2.20, 95% CI = 1.04-4.61), peer's smoking (OR = 3.11, 95% CI = 2.1-4.6), and peer's drinking alcohol (OR = 1.88, 95% CI = 1.1-3.21) were significantly associated with the presence of multiple risk behaviors among boys. Having some education (OR = 0.17, 95% CI = 0.06-0.45), and being of Hmong and Yao ethnicity (OR = 0.38, 95% CI = 0.18-0.80) were factors that protected girls from multiple risk behaviors; while peer's drinking alcohol (OR = 2.55, 95% CI = 1.59-4.09) and peer's being sexually active (OR = 2.82, 95% CI = 1.65-4.8) were significantly associated with the presence of multiple risk behaviors among girls. Conclusion There are sex, age and ethnic differences in the concurrent health risk behaviors. The influencing factors are adolescent's education and peer influence. Interventions should focus to encourage adolescents to complete the compulsory primary education as well as help them to establish friendships and follow peers with good behavior. Risk reduction messages need to take account of diverse multiple HRBs within the specific socio-cultural and gender specific context and target vulnerable adolescents such as ethnic minorities and less educated adolescents.